2020
DOI: 10.1007/s00414-020-02468-w
|View full text |Cite
|
Sign up to set email alerts
|

Comparative use of aqueous humour 1H NMR metabolomics and potassium concentration for PMI estimation in an animal model

Abstract: Estimation of the post-mortem interval (PMI) remains a matter of concern in the forensic scenario. Traditional and novel approaches are not yet able to fully address this issue, which relies on complex biological phenomena triggered by death. For this purpose, eye compartments may be chosen for experimental studies because they are more resistant to post-mortem modifications. Vitreous humour, in particular, has been extensively investigated, with potassium concentration ([K+]) being the marker that is better c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 27 publications
1
28
0
Order By: Relevance
“…Concerning the determination of the PMI, however, only a few studies that focus on the use of post-mortem CT can be found in the literature. Undoubtedly, in the past years, efforts have been made by the forensic community, including our research team, to identify methods that could help determine the time of death, such as the study of human tissues transcriptomes [29], muscle proteins degradation [30], gene expression patterns [31], ocular changes, [32,33], metabolomics [34][35][36], the study of rigor mortis using ultrasound shear wave elastography (US SWE) [37] or atomic force microscopy (AFM) [38]. However, to our knowledge, there are no studies concerning the application of fractal analysis to post-mortem CT scans for the determination of the PMI.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the determination of the PMI, however, only a few studies that focus on the use of post-mortem CT can be found in the literature. Undoubtedly, in the past years, efforts have been made by the forensic community, including our research team, to identify methods that could help determine the time of death, such as the study of human tissues transcriptomes [29], muscle proteins degradation [30], gene expression patterns [31], ocular changes, [32,33], metabolomics [34][35][36], the study of rigor mortis using ultrasound shear wave elastography (US SWE) [37] or atomic force microscopy (AFM) [38]. However, to our knowledge, there are no studies concerning the application of fractal analysis to post-mortem CT scans for the determination of the PMI.…”
Section: Discussionmentioning
confidence: 99%
“…In an attempt to overcome the ethical issue of time-dependent tissue collection, other matrices were previously proposed to study endogenous postmortem changes. These include anatomically isolated ocular fluids such as vitreous-and aqueous humor (Locci et al, 2019(Locci et al, , 2021. In these, metabolomics changes were found to progress slower and smoother than in blood and were hence proposed as a more suitable matrix for PMI estimation, but still, large enough study sets are missing for reliable PMI estimation (Zelentsova et al, 2020).…”
Section: Determination Of the Post-mortem Intervalmentioning
confidence: 99%
“…Various techniques and methods have been employed to estimate the PMI with the highest accuracy. Methods include examination of the external physical appearance; histopathological surveys [ 6 , 7 , 8 ]; reaction with a mineral acid, reaction with benzidine, nitrogen loss [ 9 ]; molecular biology [ 10 , 11 , 12 , 13 , 14 , 15 ]; metabolomics [ 16 ]; high performance liquid chromatography-tandem mass spectrometry [ 17 ]; UV-Vis spectroscopic methods [ 18 , 19 , 20 , 21 , 22 ]; radioisotope measurements [ 23 , 24 , 25 , 26 ]; luminol chemiluminescent reaction [ 24 , 27 , 28 , 29 , 30 , 31 ]; X-ray diffraction [ 32 , 33 , 34 ]; spectroscopic technology [ 21 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ]; postmortem computed tomography (CT) [ 48 ], micro-CT [ 2 , 34 ]; visible and thermal 3D imaging [ 49 ]; and entomological methods (succession model, carrion insect development) ...…”
Section: Introductionmentioning
confidence: 99%